2016
DOI: 10.1037/abn0000207
|View full text |Cite
|
Sign up to set email alerts
|

Connecting psychopathology meta-structure and mechanisms.

Abstract: A persistent challenge for the field of psychopathology has been how to best explain mental disorders and organize clinical symptoms into diagnoses. Meta-structural approaches have clarified fundamental problems and made substantial gains by using covariance structures to organize the nature of clinical symptom patterns. A remaining task is how to specify the connections between these patterns across behavioral, cognitive, and neural mechanisms. Together, meta-structural approaches and the National Institute o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Our objective was to create a data driven behavioural phenotype that could be more closely associated with the underlying intermediate neurocognitive systems than single measurement constructs. This approach resonates with the RDoC initiative to more closely align neuroscience, cognition and behavioural phenotypes [31]. Several lines of evidence support the prediction of a bifactor structure.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our objective was to create a data driven behavioural phenotype that could be more closely associated with the underlying intermediate neurocognitive systems than single measurement constructs. This approach resonates with the RDoC initiative to more closely align neuroscience, cognition and behavioural phenotypes [31]. Several lines of evidence support the prediction of a bifactor structure.…”
Section: Introductionmentioning
confidence: 92%
“…This is driven in part by the low validity inherent in the descriptive diagnostic system and the need to develop a greater understanding of the aetiologies and pathophysiologies of mental illnesses [30]. Redefining how we conceptualise the ‘surface’ characteristics of mental health in the population at large using both mental illness and mental wellness items may create a more accurate behavioural phenotype of mental states in the natural world [31]. This may in turn translate to greater precision in pinpointing the relevant genetic, neural and cognitive factors that could underlie mentally well together with ill states.…”
Section: Introductionmentioning
confidence: 99%
“…Given the contrasting findings, it is difficult to draw conclusions as to whether SAD is best represented dimensionally or categorically, or indeed a combination of both. In spite of the lack of consistency across studies, it has been suggested that the dimensional approach may afford greater utility over categorical models for refining understanding of the mechanisms of disorders such as SAD (Sanislow, 2016).…”
Section: Limitations Of the Categorical Approach To Sadmentioning
confidence: 99%
“…Initiated by NIMH in 2009, RDoC constitutes a framework for translational research that shifts the focus away from traditional DSM/ICD disorder categories and toward research on functional dimensions of behavior or cognitive/affective processes (eg, reward learning or working memory) as studied across the entire range of functioning from normal to abnormal. 1 - 3 The paradigm emphasizes the inclusion in study designs of multiple measures (eg, behavioral/cognitive, phenomenological, physiological) for examining such psychological constructs, thus promoting an integrative rather than reductionistic approach. 4 High priority is placed upon the examination of neurodevelopmental processes and environmental influences (and their interaction) in research designs.…”
Section: Introductionmentioning
confidence: 99%